Poglądy i opinie młodzieży akademickiej na temat znaczenia emisji głosu w pracy pedagoga - Kędzia , Marta; Konarczak , Agnieszka (Studia Edukacyjne, 2021)
The article deals with the issue of the importance of voice production in the work of a teacher. Incompetent voice use is one of the main factors causing disorders of the voice organ. The aim of this study is to draw attention to the issues related to voice production, presented in the context of the opinions and views of academic youth representing pedagogical fields. The text focuses on direct and indirect factors causing voice problems, disease symptoms that may appear in people working with voice, conscious work on voice projection and elements of correct speech techniques that may affect the quality of classes.